2015
DOI: 10.15690/vramn566
|View full text |Cite
|
Sign up to set email alerts
|

Ligands of RAGE-Proteins: Role in Intercellular Communication and Pathogenesis of Inflammation

Abstract: The review contains data on the diversity of endogenous ligands of RAGE receptors (receptor for advanced glycation end products) that play an important role in the signal transduction in (patho) physiological conditions. RAGE takes part in various physiological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…It significantly increases the expression of IL-1β, IL-6, and TNF-α by stimulating peripheral blood mononuclear cells, inducing TLR4-mediated inflammatory signaling in mononuclear cells and activating transcription factor (NF)-κ B, extracellular signal-regulated kinase 1/2, and P38 [ 21 ]. S100A4 multimers (active form) can also stimulate synovial fibroblasts and regulate apoptosis [ 22 ]. These results suggest that S100A4 activates immune and inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It significantly increases the expression of IL-1β, IL-6, and TNF-α by stimulating peripheral blood mononuclear cells, inducing TLR4-mediated inflammatory signaling in mononuclear cells and activating transcription factor (NF)-κ B, extracellular signal-regulated kinase 1/2, and P38 [ 21 ]. S100A4 multimers (active form) can also stimulate synovial fibroblasts and regulate apoptosis [ 22 ]. These results suggest that S100A4 activates immune and inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular S100B is associated with RAGE signaling in chondrocytes, which may be the mechanism underlying osteogenesis in RA [ 22 ]. S100A8/A9 induces proteoglycan decomposition, chondrocyte apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the interactions between microglia and other cell types, including neurons, astrocytes, endothelial cells, and stem cells, as well as the underlying mechanisms, are complex, and these might involve intriguing roles of the receptor of advanced glycation end products (RAGEs), S100B, high-mobility group box 1 (HMGB1), and NADPH oxidase . RAGE, a cell-surface receptor that can bind to various ligands, including advanced glycation end products (AGEs), HMGB1, S100 proteins, and amyloid-β (Aβ), is mainly expressed in cortical and spinal motor neurons, astrocytes, microglia, and endothelial cells and is expressed at a high level in the developing nervous system. In adult animals, RAGE is expressed at a low level under physiological conditions but is drastically increased under chronic inflammation because of the accumulation of various RAGE ligands. ,, With regard to cerebral ischemia, the results of in vitro and in vivo experiments have indicated that RAGE expression in brain tissues or nerve cells is increased after hypoxic injury in a time-dependent manner , and is associated with neuronal apoptosis and the severity of cerebral infarction, , and this increase has been confirmed in stroke patients; moreover, the increased RAGE expression probably accelerates ischemia-induced neuronal death through activation of inflammatory pathways. These findings indicate that RAGE potentially plays a critical role in cerebral infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the pro‐ and anti‐inflammatory cells and mediators, RAGE (Receptor for Advanced Glycation Endproducts), a receptor capable of interacting with signaling molecules, are involved in the inflammatory process (Deane et al, 2004; Kierdorf and Fritz, 2013). RAGE comprises one of the receptors for non‐enzymatic non‐glycated adducts (AGEs), playing a key role in the inflammatory process because of their interactions and the ability to induce secretion of cytokines and chemokines (Schmidt et al, 2001; Uspenskaya et al, 2015). RAGE is considered a key mediator of several physiological, as well as pathological (e.g.…”
Section: Introductionmentioning
confidence: 99%